2019
DOI: 10.1044/2019_aja-18-0194
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Language History on Sentence Recognition in Noise or Two-Talker Speech: Monolingual, Early Bilingual, and Late Bilingual Speakers of English

Abstract: Purpose Language history is an important factor in masked speech recognition. Listeners who acquire the target language later in life perform more poorly than native speakers. However, there are inconsistencies in the literature regarding performance of bilingual speakers who begin learning the target language early in life. The purpose of this experiment was to evaluate speech-in-noise and speech-in-speech recognition for highly proficient early bilingual listeners compared to monolingual and late… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 50 publications
1
16
0
Order By: Relevance
“…Several studies have investigated bilinguals' performance in competing speech tasks, usually in comparison to monolingual participants when the target is presented in a single language (Van Engen, 2010;Calandruccio & Zhou, 2014;Regalado, Kong, Buss & Calandruccio, 2019). Van Engen (2010) and Calandruccio and Zhou (2014) found that simultaneous bilingual participants performed better when the masker language differed from the target language, consistent with the pattern observed for monolingual participants.…”
Section: Bilinguals and Competing Speech Tasksmentioning
confidence: 77%
See 4 more Smart Citations
“…Several studies have investigated bilinguals' performance in competing speech tasks, usually in comparison to monolingual participants when the target is presented in a single language (Van Engen, 2010;Calandruccio & Zhou, 2014;Regalado, Kong, Buss & Calandruccio, 2019). Van Engen (2010) and Calandruccio and Zhou (2014) found that simultaneous bilingual participants performed better when the masker language differed from the target language, consistent with the pattern observed for monolingual participants.…”
Section: Bilinguals and Competing Speech Tasksmentioning
confidence: 77%
“…Van Engen (2010) and Calandruccio and Zhou (2014) found that simultaneous bilingual participants performed better when the masker language differed from the target language, consistent with the pattern observed for monolingual participants. On the other hand, Regalado et al (2019) found that monolingual, simultaneous bilingual, and late bilingual (L1 Mandarin, L2 English) participants performed better with noise maskers as opposed to speech maskers (all targets and speech maskers were presented in English) but they did not investigate the role of masker language.…”
Section: Bilinguals and Competing Speech Tasksmentioning
confidence: 93%
See 3 more Smart Citations